Differences in the association between the 2018 ACGIH TLV for Hand Activity and carpal tunnel syndrome by gender and age. (September 2021) - Harris-Adamson, C; Meyers, A; Bonfiglioli, R; Kapellusch, J; Dale, AM; Thiese, M; Fethke, N; Eisen, EA; Bao, S; Evanoff, B; Hegmann, K; Gerr, F; et al.
The recently revised ACGIH TLV for Hand Activity (TLV2018) is a widely used tool for assessing risk for upper limb musculoskeletal disorders. The purpose of this analysis was to compare the strength of the exposure-response relationships between the TLV2018 and carpal tunnel syndrome (CTS) between men and women and across age strata. Heterogeneity of the effect size by sex or age would be important to specialists using the method for prevention of CTS among working populations. Data from two large prospective studies were combined to allow for stratification of exposure-response models assessing the association between the TLV2018 and CTS by gender and age. Results show greater risk for women than men and for younger workers than older workers for TLV2018 values above the action limit. Although the TLV2018 is an effective surveillance tool for estimating increased risk of CTS with increasing exposure, these analyses show that such increase are not homogeneous across sex and age.